Banking on the Principles: Compliance with Basel Core Principles and Bank Soundness - Demirguc-Kunt, Asli (2012)
This study finds that banks receive more favorable Moody's financial strength ratings in countries with better compliance with Basel Core Principles related to information provision. The results are robust to controlling for broad indexes of institutional quality, macroeconomic variables, sovereign ratings, and reverse causality. Compliance with other Core Principles does not affect ratings robustly. Measuring bank soundness through Z-scores yields broadly similar results for advanced and emerging markets. Countries aiming to upgrade banking regulation and supervision should consider giving priority to information provision over other elements of the core principles.